Causality Between Energy Consumption and Economic Growth: The Case of Kuwait - Al-Zuhair, Mohammad; AL-Bazali, Talal (International Journal of Energy Economics and Policy, 2022)
The causality relationship between energy consumption and economic growth for Kuwait was investigated in this study, and the impact of increasing local energy prices on Kuwait’s economic growth was examined. Our methodology relied on statistical analyses to study the causality trends between various factors such as GDP; annual oil production; oil-reserves depletion; annual energy consumption; and CO2 annual emission, to formulate a hypothesis that determine the actual causality relationship between GPD and energy consumption without having to use the already-established statistical methods. Results showed no solid foundation to support the application of growth or conservation hypothesis. Results support the neutrality hypothesis which specifies no causality relationship between energy consumption and economic growth (GDP), especially from the year 2007/2008 and beyond, which allows for adopting stricter local-energy prices with no effect on the overall economic growth of the country. Results showed, however, a close relationship between oil exports (sales) and total GDP for Kuwait. The difference between total GDP and oil GDP exactly equals the non-oil related economic growth contribution to the country’s economy. The findings of this study provide reliable and suitable basis for policymaking not only in Kuwait, but also in other single-source oil-producing countries such as GCC countries.